2018
DOI: 10.1002/mgg3.481
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the mutation spectrum of PAX6 from three Chinese congenital aniridia families and identification of male gonadal mosaicism

Abstract: BackgroundCongenital aniridia is a severe autosomal dominant binocular developmental disorder, the primary feature of which is congenital absence or hypoplasia of the iris. PAX6 is the main disease‐causing gene of congenital aniridia; inheritance is autosomal dominant. But the current mutations do not fully explain this disorder.MethodsWe investigated the mutation profile of genes related in three Chinese families with congenital aniridia through targeted sequencing technology. And we validated the candidate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Quantitative analysis of parental PAX6 gene showed that all of the proband's fathers have mutant allele fractions that range from 13 to 29%, depending on the tissue analysed, and have mild or no ocular features as compared to their affected offspring. Similarly, Bai et al reported the presence of male gonadal mosaicism in a Chinese family with aniridia caused by PTC-inducing mutation c.879_880delCA, p.Ser294Cysfs*46 [109].…”
Section: Inheritance Of Pax6 Mutationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Quantitative analysis of parental PAX6 gene showed that all of the proband's fathers have mutant allele fractions that range from 13 to 29%, depending on the tissue analysed, and have mild or no ocular features as compared to their affected offspring. Similarly, Bai et al reported the presence of male gonadal mosaicism in a Chinese family with aniridia caused by PTC-inducing mutation c.879_880delCA, p.Ser294Cysfs*46 [109].…”
Section: Inheritance Of Pax6 Mutationsmentioning
confidence: 86%
“…Recent studies reported that the rate of mosaicism could be as high as 17.5% among apparent de novo cases for different dominant disorders [83,107]. Indeed, several reports have suggested mosaicism as the cause for the variable phenotypes seen in some sporadic PAX6-affected patients [83,93,108,109]. A recent study from Tarilonte et al proved the existence of post-zygotic parental mosaicism in three unrelated Spanish families with variable aniridia or microphthalmia phenotypes caused by heterozygous nonsense (c.771G>A, p.Trp257* and c.120C>A, p.Cys40*) or missense (c.178T>C, p.Tyr60His) PAX6 mutations, respectively [110].…”
Section: Inheritance Of Pax6 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that occurrence of PAX6 mutations may result in the development of aniridia, which constitutes a severe panocular eye disease associated with iris hypoplasia [177][178][179][180]. There are several research data confirming a direct correlation of PAX6 gene mutation with aniridia occurrence [181][182][183][184]. Interestingly, it has been reported that aniridia is frequently correlated with glaucoma and glaucoma associated with aniridia may trigger a progressive loss of vision [185].…”
Section: Ntf4mentioning
confidence: 99%